Assessing the impact of incomes policy: The italian experience - Francesco Pastore (Institute for the Study of Labor (IZA), 2010)
The Saint Valentine's decree (1984) and the ensuing hard fought referendum (1985), which reduced the automatisms of scala mobile, started a process of redefinition of wage fixing in Italy, which culminated with the final abolition of scala mobile (1992) and the approval of Protocollo d'intesa (1993). Since then, following New Corporatist principles, a national system of centralised wage bargaining (concertazione) and the so-called institutional indexation have governed the determination of wages. This paper aims to assess the impact of such incomes policy agreements on the long and short run equilibrium relationship between real wages, labour productivity and unemployment. Different time series econometric tools confirm that incomes policy has altered the relationship between real wages and productivity, generating not only a permanent downward impact on prices, but also on real wages. In a sense, incomes policy has caused a new form of (upward) wage rigidity. Interestingly, no impact of incomes policy on the weak relationship between real wages and unemployment is detected. The analysis calls for a careful revision of the 1993 Protocol aimed at: a) better protecting the purchasing power of real wages without losing control on inflation; b) introducing growth generating mechanisms.
Keywords: C22; E12; E25; E64; E65; 330; New Keynesian macroeconomic theory; neo-corporatism; models of industrial relations; Phillips Curve; incomes policy; centralised wage bargaining; macroeconomic policy evaluation; income distribution; cointegration analysis; structural break testing; scala mobile; Protocollo d'intesa; Italy